(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
The article presents the peculiarities of business activities of enterprises operating in the Republic of Armenia (RA) offering heritage- and cultural-based experiential tourism (HCBET) products and services. The article proposes the content of an integrated Business Canvas Model for enterprises engaged in similar activities. The integrated business canvas is based on the study of the cases of the enterprises selected within the framework of the research, according to the following key factors: Thematic areas, Activities/services, Marketing approach, Financing methods, Key success factors and challenges, and Potential for future development. Enterprises, operating in this field, are considered key cells of this kind of tourism development in the RA. Those enterprises are considered social organisms, which, if properly managed and provided with appropriate support, can become the basis for the long-term development of this kind of tourism in the RA. Therefore, it is necessary to systematically present the system of tourism services and products of enterprises included in the HCBET and the generalized model of business activity. It is important to emphasize that HCBET in the RA mainly includes hotel and restaurant businesses that mainly offer experiences based on Armenian intangible cultural heritage.